Rapidly developing, large pyogenic liver abscesses in the setting of pancreatic cancer. Issue 4 (4th July 2021) - Kwon, Joshua; Pruden, Kathryn; Mohseni, Michael M.
Abstract: We report a case of multiple, giant, polymicrobial pyogenic liver abscesses that developed within 3 months in a patient with a recent pancreatic cancer diagnosis. He presented with fatigue, abdominal distension, abdominal pain, dyspnea, and lower extremity edema and was treated with intravenous antibiotics and percutaneous hepatic abscess catheter placement. Abscess fluid cultures were polymicrobial. Unfortunately, he developed septic shock with bacteremia and multiorgan failure and died after 6 days of hospitalization. Pyogenic liver abscesses are increasingly common in the United States, especially those associated with malignancy.